Telocytes of the male reproductive system: dynamic tissue organizers - Sanches, Bruno D. A.; Rocha, Lara C. [UNESP]; Neto, J. Pimentel [UNESP]; Beguelini, Mateus Rodrigues; Ciena, Adriano P.; Carvalho, Hernandes F. (Frontiers, 2024)
Telocytes are CD34+ interstitial cells that have long cytoplasmic projections (called telopodes), and have been detected in several organs, including those of the male reproductive system. In this brief review we evaluate the role of telocytes in tissue organization of the different organs of the male reproductive system in which these cells were studied. In general terms, telocytes act in the tissue organization through networks of telopodes that separate the epithelia from the stroma, as well as dividing the stroma into different compartments. In addition to this contribution to the structural integrity, there is direct and indirect evidence that such “walls” formed by telocytes also compartmentalize paracrine factors that they or other cells produce, which have a direct impact on morphogenesis and the maintenance of organ cell differentiation, as well as on their normal physiology. Moreover, alterations in telocytes and telopode networks are correlated with pathological conditions in the male reproductive system, in response to profound changes in structural organization of the organs, in inflammation, hyperplasia and cancer. Further studies are necessary to evaluate the molecular pathways telocytes employ in different contexts of physiology and disease.
Keywords: castration; paracrine factors; prostate cancer; smooth muscle; stromal compartmentalization; telopodes; testes; tissue organization